How many lymph nodes should be dissected in esophagectomy with or without neoadjuvant therapy to get accurate staging?. Issue 1 (17th April 2019) - Zhan, C; Shi, Y; Jiang, W; Sun, F; Li, M; Lu, T; Yin, J; Ma, K; Yang, X; Wang, Q
SUMMARY: It is essential to dissect an adequate number of lymph nodes (LNs) to ensure staging accuracy during esophagectomy with or without neoadjuvant therapy. We developed a statistical model to quantify the probability of precise nodal staging based on previous studies. Esophageal cancer patients who underwent esophagectomy were retrospectively reviewed in the Surveillance, Epidemiology, and End Results database. A β-binomial distribution was adopted to estimate the number of understaged patients based on the numbers of positive and examined LNs. Using 6, 252 patients, we estimated a 90% confidence of accurate N0 staging could be achieved by examining 17 LNs without neoadjuvant therapy. To obtain similar accuracy in N1 and N2, 20 and 25 LNs should be examined. For patients with neoadjuvant therapy, 18, 19, and 28 LNs could achieve the same accuracy. Staging accuracy was a significant prognostic factor. We found when 90% confidence had been achieved, patient survival did not improve with more LNs examined and the ratio and log odds of positive LNs did not have significant prognostic values. The statistical model we developed for precise staging in patients with different N stages is of great value in guiding lymphadenectomy. It provided risk assessment for underestimated LN metastases and guided subsequent adjuvant treatment.